2002
DOI: 10.1046/j.1365-2672.2002.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

An arsenic(III)-oxidizing bacterial population: selection, characterization, and performance in reactors

Abstract: Aims: To select an autotrophic arsenic(III)-oxidizing population, named CASO1, and to evaluate the performance of the selected bacteria in reactors. Methods and Results: An As(III)-containing medium without organic substrate was used to select CASO1 from a mining environment. As(III) oxidation was studied under batch and continuous conditions. The main organisms present in CASO1 were identified with molecular biology tools. CASO1 exhibited significant As(III)-oxidizing activity between pH 3 and 8. The optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(101 citation statements)
references
References 21 publications
1
100
0
Order By: Relevance
“…Osborne et al, 2010). Several pure cultures of bacterial strains (Rhine et al, 2006), as well as microbial consortia (Battaglia-Brunet et al, 2002) able to transform As (III) to As(V) have been isolated. For some of them, biogeochemical function in the environment has been described (Connon et al, 2008;Drewniak et al, 2010) and/or a practical application in bioremediation has been proposed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Osborne et al, 2010). Several pure cultures of bacterial strains (Rhine et al, 2006), as well as microbial consortia (Battaglia-Brunet et al, 2002) able to transform As (III) to As(V) have been isolated. For some of them, biogeochemical function in the environment has been described (Connon et al, 2008;Drewniak et al, 2010) and/or a practical application in bioremediation has been proposed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation reaction of arsenite to arsenate depends on pH. At pH<2.0, the oxidation reaction is represented as follows 10) . The standard free-energy change for this reaction is -129.65 kJmol −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Battaglia-Brunet, et al 10) found that the biofilm on the internal surface of the glass reactor developed as CASO1 oxidized arsenite, and considered that the high oxidation rate may have resulted from the presence of this biofilm. In this study, the formation of aggregates was observed as the arsenite oxidation proceeded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some As(III)-oxidizing bacteria are able to oxidize As(III) at low pH (≤4), e.g., Sulfolobus acidocaldarius (Sehlin and Lindstrom, 1992) and Thiomonas arsenivorans (Dastidar and Wang, 2009). An autotrophic As(III)-oxidizing population (CASO1) was isolated that exhibited As(III) oxidation activity between pH 3-8 (Battaglia-Brunet et al, 2002). However, most of the known As(III)-oxidizing bacteria demonstrated optimum oxidation at near-neutral pH.…”
Section: As(iii)-oxidizing Bacteriamentioning
confidence: 99%